Molecular Iodine‐Mediated Domino Reaction for the Synthesis of Benzamides, 2, 2‐Diazidobenzofuran‐3(2H)‐ones and Benzoxazolones. Issue 18 (12th December 2013) - Rajendar, K.; Kant, Ruchir; Narender, T.
Abstract A simple and efficient domino protocol has been developed for the preparation of biologically important benzamides, 2, 2‐diazidobenzofuran‐3(2H)‐ones and benzoxazolones from various structurally and electronically divergent acetophenones and ortho‐hydroxyacetophenones in the presence of molecular iodine, sodium azide and sodium bicarbonate at 100 °C in good to excellent yields. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>